Vernakularisme, Informalitas, dan Urbanisme: Café sebagai Ekspresi Gaya Hidup Kontemporer - Rr. Dhian Damajani (ITB Journal Publisher, LPPM ITB, 2008)
The word café originated from coffee, which is commonly used to describe a place where one drinks coffee, i.e. coffeehouse. Generally, this place is not too large in space providing drinks and snacks, as well as accommodates other activities for use either in the morning or late afternoon. This habit of coffee-drinking is carried out by societies in various countries around the world, including in Indonesia. This research explores cafés that embed to the local context of Bandung as case studies. This is due to the increase number of cafés in Bandung during the early 2000s which demostrate conditions that are unique and perhaps unfounded in other places of Indonesia. There are 5 (five) design variables that illustrate the diversity of cafés in Bandung: (1) Scale (café dimensions), (2) Class (low, medium, high economic-level), (3) Type (internet-café, bookstore-café, music-café, gallery-café etc), (4) Location (part of a commercial area, in one’s front yard, along the street, within a public open space), as well as (5) Time (morning, afternoon, late afternoon, evening, or more than one period of time). It is found that cafés in Bandung have developed beyond the boundaries of their origin and denotative meanings. Their existences have become part of the everyday life of the society, it serves not only as a place to chat and spend free time during late afternoons, but also as transactional-spaces that accommodate diverse activities. Referring to Barbara Kirschenblatt-Gimblett [1] this situation illustrates the phenomenon of urban vernacularism that is marked by the following characteristics: sporadic, self produced, absence of author and creator identity, as well as free from any formal pressure.